The Coal Commission Reports and the Coal Situation - Hammond, M. B. (Quarterly Journal of Economics, 1924)
Importance of the coal problem, 541. — I. Occasion for appointment of the Commission, 543. — The Federal Act of October, 1923, 547. — Personnel of the Commission, 548. — II. The bituminous branch of the industry; striking irregularity of production, 550. — The causes: seasonal demand, strikes, overdevelopment above all, 551. — Effects on labor, 559. — No radical remedy proposed by the Commission, 660. — Changes in railroad car distribution recommended, 561. — Readjustment of freight rates, 563. — The Commission fails to urge the use by the Interstate Commerce Commission of its power to veto building of lines or sidings not needed, 565. — III. Anthracite coal problems simpler, 566. — The fundamental problem is that of monopoly, 568. — The Commission proposes a graded tax on royalties, 570. — IV. Unionization and non-union fields, 572. — The Commission on the whole commends the United Mine Workers, condemns operators in non-union fields, yet takes a neutral attitude, 573. — V. The Reports have high educational value, the remedies suggested are inadequate, 577. — Some more far-reaching plan must come, 581.